Development of on-site detection device for pathogenic Leptospira spp. in stream water / Dzulaikha Khairuddin - Khairuddin, Dzulaikha (2019)
Worldwide, the popularity of recreational activities which involve contact with water has grown. Moreover, ease of travel has altered the public use of water for recreational purposes. The adverse impacts of recreational use of freshwater environments upon the health of users must be weighed against the enormous benefits to health and well-being. Recreational area always associated with the use of this environment for rest, relaxation and exercise. In Malaysia, in addition to being the focus for leisure, recreational area is also a focus for family activities like picnics and grills and other activities such as camping group of students. Contaminated water with pathogenic Leptospira will pose a hazardous threat to deadly disease infections if not detected early. The case of death from Leptospirosis is a great concern for a tropical country like Malaysia. The warm and humid climate throughout the year in Malaysia is a favour of Leptospira leading to longer survival. Any water bodies such as streams, stagnant water, bogs, ponds and puddles are natural habitats for Leptospira. The survival of this bacteria mostly depends on high humidity with neutral pH (6-7.5). In addition to natural habitats, the presence of Leptospira in the water is also due to the excreted of urine of Leptospira infected animals. Humans are infected either directly through contact with infected urine or indirectly through contaminated water or soil. The bacteria enter the body through wounds and abrasions of the skin and through the mucosal surface of the mouth, nose and conjunctiva. In recent years, the case of Leptospirosis that occurred after exposure to recreational activities in the waterfall area seemed like no solution. Most cases are often critical or delayed, leading to a lot of loss of life. So many of these unwanted events should be a signal that detailed investigations to prevent the occurrence of an infection should be implemented. Action should be taken to reduce the Leptospira infection during recreational water activities.